How to Formulate Marketing and Sales Strategy through Analytical CRM for An Elevator Company - Teoh, Cheok Hui (2010)
This paper aims to examine how to formulate marketing and sales strategy through analytical Customer Relationship Management (CRM) systems for an elevator company. A multi-layered framework with different perspective of affordance, weighting, interoperability are applied to the culture, people, processes and technology layer as proposed in the framework. Evidence from the case study of Company S suggest that the multi-layered and interdisciplinary framework can assist an elevator company in developing their own CRM strategy through greater understanding of themselves and their customers in a rapid changing environment. The overall results of this study disclosed that marketing capability provide a possibility of the association between CRM technology use and formulation of organisation marketing and sales strategy. Moreover, a customer-centric organisational culture and management information system will facilitate the usage of CRM technology. This study provides an overview of how an elevator company could make use of this CRM framework to identify its’ own organisation blind spot especially on the cultural aspects that hindered it from becoming customer-centric organisation and at the same time creating a marketing and sales strategy which would suit them.